Activation of transient receptor potential vanilloid 4 involves in hypoxia/reoxygenation injury in cardiomyocytes - Wu, Qiong-Feng (Cell Death Dis, 2017)
Transient receptor potential vanilloid 4 (TRPV4) is highly expressed in heart and vessels and can be activated during myocardial ischemia/reperfusion (I/R). Recently, we found that treatment with a selective TRPV4 antagonist HC-067047 significantly reduced infarct size, decreased troponin T levels and improved cardiac function in murine model myocardial I/R. This study was undertaken to investigate the mechanism underlying TRPV4-mediated myocardial I/R injury. To mimic myocardial I/R injury, we established a hypoxia/reoxygenation (H/R) model in H9C2 cells and neonatal rat ventricle myocytes (NRVMs) in vitro. TRPV4 mRNA and protein expression was confirmed in the H9C2 and NRVM, whereas functional TRPV4 activity was assessed from Ca(2+) influx response to a TRPV4 agonist GSK1016790A. TRPV4 functional expression was significantly enhanced during H/R. Furthermore, H/R increased the intracellular Ca(2+) concentration ([Ca(2+)](i)) and induced cell injury, which were reversed by HC-067047 but was further aggravated by GSK1016790A. Moreover, HC-067047 treatment significantly alleviated the increase of reactive oxygen species (ROS) generation, the depolarization of mitochondrial membrane potential (Δψm) and the opening of mitochondrial permeability transition pore (mPTP) during H/R. On the contrary, GSK1016790A exacerbated those effects. Meanwhile, increase in [Ca(2+)](i) and ROS induced by activation of TRPV4 was almost abolished when cells were cultured in Ca(2+)-free medium. In addition, ROS scavenger NAC obviously reversed activation of TRPV4-induced changes of Δψm and mPTP opening. Finally, we confirmed the direct roles of TRPV4 on cardiac injury and ROS generation in murine model myocardial I/R in vivo. In conclusion, activation of TRPV4 induces Ca(2+) influx in cardiomyocytes, with subsequent ROS release, depolarizing of Δψm, opening mPTP, inducing injury and TRPV4 has key roles during I/R via these pathways.